Knowledge, Attitude and Diagnosing Ability about Oral Cancer among Medical and Dental Students of a Tertiary Medical College in Chitwan, Nepal - Ghosh, Snehashish; Bhattarai, Rosina; Mahanta, Swagat Kumar; Adhikari, Sushmita (Journal of College of Medical Sciences-Nepal, 2024)
Background Oral cancer is one of the most common cancers taking away many lives worldwide. The chances of recovery from oral cancer are good if, detected early. Lack of knowledge, casual attitude, and poor diagnostic skills among medical and dental undergraduate students could delay detection and management. The present study aims to assess and compare the knowledge, attitude, and diagnostic ability of oral cancer among medical and dental undergraduate students in a tertiary care hospital in Chitwan, Nepal. Methods A comparative cross-sectional study was conducted among 123 (medical- 72, dental- 51) undergraduate students using a pre-fabricated questionnaire with close-ended questions and the responses were recorded in Excel sheets. The recorded responses were analyzed using Statistical Package of Social Sciences (SPSS) software. A chi-square test was performed to analyze the difference in knowledge, attitude, and diagnostic ability among medical and dental undergraduate students. Results The response rate for the study was 96.09%. The study revealed over 80% adequacy of knowledge of oral cancer among the participants. 92.41 % of medical students and 96.45 % of dental students showed a positive attitude towards oral cancer. However, a difference was noted in the diagnostic ability of oral cancer among medical and dental students. 93.13% of dental undergraduates were confident about diagnosing oral cancer whereas the confidence of medical undergraduates was only 40.96%. Conclusions The study highlighted the need to educate medical and dental undergraduates about oral cancer and emphasized the need for the revision of the medical curriculum to improve their confidence in their diagnostic ability of oral cancer.